SEMIOTIC ANALYSIS OF GESTURES IN DAILY LIFE COMMUNICATION FROM THE FILM “THE SILENCE” - Zuhri, Jamilah; Sunra, La (Faculty of Languages and Literature, Universitas Negeri Makassar, 2025)
Semiotics in general is a sign, symbol, and meaning that exists in our daily lives. Especially in gestures which are also related to gestures and semiotics. Gestures are nonverbal movements with the aim of communicating. The bond between semiotics and gestures here is to be able to understand the meaning of these nonverbal movements so that communication can be smoother. This research uses Mcneill's theory (2005) to find out what types of gestures will be in the nonverbal scenes in the movie “The Silence”. And also this research uses the triadic triangle theory in Charles Sanders Peirce's theory to determine the meaning or meaning of the movements that appear in the scene in the movie. This analysis aims to know more about gestures in the semiotic approach. This research uses descriptive qualitative with Visual Research Method or VRM as a supporting method. According to the results of the analysis, researchers found several types of gestures from 13 Iconic, 4 Metaphoric, 10 Deictic, and 2 for Beat data. There are 28 data observed, we concluded that gestures are very important for our daily lives, because the feelings that come out of body movements never lie. Gestures can also complement verbal communication, and for the communication of people who use sign language. We also concluded that gestures in everyday life found in the movie “The Silence” have no differences in our daily gestures in communicating in Indonesian and American culture.